Association of Umbilical Cord Milking vs Delayed Umbilical Cord Clamping With Death or Severe Intraventricular Hemorrhage Among Preterm Infants. Issue 4 (April 2020) - Katheria, Anup; Reister, Frank; Essers, Jochen; Mendler, Marc; Hummler, Helmut; Subramaniam, Akila; Carlo, Waldemar; Tita, Alan; Truong, Giang; Davis-Nelson, Shareece; Schmölzer, Georg; Chari, Radha; et al.
Abstract : (Abstracted from JAMA 2019;322(19):1877–1886) Delayed umbilical cord clamping is the current standard of care for newborn management at delivery. The extended time between delivery and umbilical cord clamping allows for a higher quantity of placental blood to reach the newborn.